PENGARUH KONFLIK PERAN, KONFLIK KERJA, AMBIGUITAS PERAN DAN STRES KERJA TERHADAP KINERJA KARYAWAN PT.MULIA KARYA PRIMA KOTA BATU - Wildan Ridza Sidani; Abd kodir Djaelani; M Khoirul ABS (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRAKThis research was conducted at PT. KARYA PRIMA Batu City. The purpose of this study was to examine and analyze the effect of role conflict, work conflict, job ambiguity and work stress on the performance of employees of PT. KARYA PRIMA Batu City. The variables used are the influence of role conflict, work conflict, job ambiguity and job stress as independent variables, while the employee performance variable is the dependent variable. The sample used in this study was 40 employees, using the saturated sample method. Data collection methods by collecting primary and secondary data. The analysis used includes instrument testing, classical assumption test, multiple linear regression, determination coefficient test, hypothesis testing and determination coefficient test using multiple regression analysis with SPSS 14.0 assistance for software. The results showed that the variable role conflict and role ambiguity had no significant effect on the performance of PT. KARYA PRIMA Kota Batu, while the variables of work conflict and job stress have a significant effect on the performance of the employees of PT. KARYA PRIMA Batu City, and the overall variables of role conflict, work conflict, role ambiguity and job stress have a significant effect on the performance of employees of PT. KARYA PRIMA Batu CityKeywords : Role Conflict, Work Conflict, Role Ambiguity, Work Stress, Employee Performance